Optimizing the Performance of SI Engine with Velocity Stack - Kuncara, Martina (Jurnal Fakultas Teknik Kuningan, 2024)
Improving the performance of a spark ignition (SI) engine aims to enhance the efficiency of the engine through various modifications or changes. One way to enhance the performance of an SI engine is by modifying the air intake system with the addition of a velocity stack to increase the airflow into the engine. This study conducted direct experiments on a 150cc SI engine, measuring power and torque, to examine the effects of using a velocity stack. The research results indicate improvements in engine performance with the use of a short velocity stack, resulting in a 6.2% increase in power and a 6.4% increase in torque. Meanwhile, the use of a long velocity stack increased power by 9.3% and torque by 11%. The characteristics of using a long velocity stack provide rapid acceleration and high torque at low to mid-range RPM compared to using a short velocity stack, which is more responsive to torque at higher RPM, enabling the engine to reach its maximum top speed. The use of a velocity stack improves volumetric efficiency, thus significantly influencing engine performance enhancement.